Activation of Central Angiotensin Type 2 Receptors by Compound 21 Improves Arterial Baroreflex Sensitivity in Rats With Heart Failure - Gao, Juan (Am J Hypertens, 2014)
BACKGROUND: In a previous study we demonstrated that central administration of compound 21 (C21), a nonpeptide AT2R agonist, inhibited sympathetic tone in normal rats. In this study, we hypothesized that C21 exerts a similar effect in rats with coronary ligation–induced heart failure (HF). METHODS: C21 was intracerebroventricularly infused for 7 days by osmotic mini pump. Blood pressure (BP) and heart rate (HR) were recorded by radiotelemetry in the conscious state to measure spontaneous arterial baroreflex sensitivity. Urine was collected for measurement of norepinephrine excretion. On the last day of C21 treatment, renal sympathetic nerve activity, BP, and HR were directly recorded under anesthesia, and the induced arterial baroreflex sensitivity was evaluated. Protein expressions of neuronal nitric oxide synthase (nNOS) and angiotensin II type 1 receptor (AT1R) in the subfornical organ, paraventricular nucleus, rostral ventrolateral medulla, and nucleus tractus solitarius were determined by Western blot analysis. RESULTS: C21-treated HF rats displayed significantly less norepinephrine excretion (2,385.6±121.1 vs. 3,677.3±147.6ng/24 hours; P < 0.05) and lower renal sympathetic nerve activity (50.2±1.9% of max vs. 70.9±8.2% of max; P < 0.05) than vehicle-treated HF rats. C21-treated rats also exhibited improved spontaneous arterial baroreflex sensitivity and induced arterial baroreflex sensitivity. Bolus intracerebroventricular injection of angiotensin II–evoked pressor and sympatho-excitatory responses were attenuated in the C21-treated HF rats, which displayed upregulated nNOS and downregulated AT1R expression in the subfornical organ, paraventricular nucleus, and rostral ventrolateral medulla. CONCLUSIONS: Activation of central angiotensin II type 2 receptor AT2R by C21 suppresses sympathetic outflow in rats with HF by improving baroreflex sensitivity and may provide important benefit in the HF syndrome.